Re-consider the distinction of liberty - Singh, Mayavee (Видавництво Львівської політехніки, 2011)
Berlin in his book Four Essays on Liberty, he firstly explains historically how others define liberty and after that Berlin distinguishes liberty in two senses – negative and positive. He analyses both sense – negative and positive though he emphasizes that negative sense is a better option. In this paper an attempt has been made to analyse and reconsider the distinction between negative and positive notion of liberty.
Переосмислення характерних рис свободи
Keywords: liberty; Berlin; freedom; individual; self; choice